Uji Deteriorasi Terkontrol (UDT) ‎untuk Memperkirakan Masa Simpan Benih Kedelai (Glycine max (L.) Merr.) - Pepi Nur Susilawati; Anis Andrini; Evi Dwi Sulistya Nugroho; Ulima ‎ Darmania Amanda (agriTECH, 2019)
Deterioration of seeds during storage may reduce the supply of high-quality seeds which become the limiting ‎factor of soybean production in tropical countries. Controlled Deterioration Test (CDT) is one of the ‎fastest vigor testing methods. The objective of this study was to achieve the suitable moisture content and ‎duration of CDT treatment in soybean seed, then establish a model that associated with the seed vigor in ‎the field after a certain time of storage. Split-plot with 2 factors, namely seed varieties and the combination of ‎moisture content and heat exposure duration were used to determine the influence of CDT treatment. ‎Another split-plot for 2 factors, namely storage period and seed varieties were used to determine the effect ‎of shelf life. Viability parameters were observed by germination strength (GS) and seedling vigor index (VI), ‎using a rolled paper towel method. The results showed that there was an interaction between soybean seed ‎varieties and the combination of seed moisture content treatment with duration of CDT exposure. Sindoro ‎and Tanggamus varieties had higher viability and storability than other varieties. Combinations of 28% seed ‎moisture content for 24 hours CDT duration were sensitive enough to evaluate the physiological potential of ‎soybean seeds, providing information that was closely related to seed germination after stored for 1 month. ‎